PENAMBAHAN PATI BIJI NANGKA (Artocarpus heterophyllus lamk) TERHADAP KUALITAS KIMIA BAKSO AYAM - Astuti, Farida Kusuma; Tribudi, Yuli Arif (Fakultas Pertanian, Universitas Sam Ratulangi, 2017)
The purpose of this research was find out the chemical of meatball with addition of different concentration of jackfruit seeds starch(0%, 10%, 20% and 30%). The result showed that addition of jackfruit seeds starch showed significant effect (P<0.05) to protein content but not significant (P>0.05) effect for the chemical content (water content, ash, fat), but increased levels of dietary fiber along with addition of different concentration of jackfruit seeds starch. Based on the chemical properties, it can be concluded that the 30% concentration of jackfruit seeds starch replace tapioca flour function as elasticy agent, but in general it is favoredKeywords : meatball, jackfruit seeds starch, meat chicken